Market structure and efficiency performance of ASEAN banks / Rossazana Ab-Rahim, Vimal Prakash Rao Subramaniam and Sonia Kumari Selvarajan - Ab-Rahim, Rossazana; Subramanian, Vimal Prakash Rao; Selvarajan, Sonia Kumari (Accounting Research Institute (ARI), 2020)
The aim of this study was to investigate market structure and efficiency performance of the ASEAN banking market during the study period of 2011 - 2016. In order to assess the market structure of commercial banks in ASEAN, the Herfindahl-Hirschman index (HHI) was used while the efficiency performance which consists of technical efficiency, pure technical efficiency and scale efficiency were measured using Data Envelopment Analysis (DEA). The results showed that the banking sector in Malaysia, Thailand and Philippines are moderately concentrated while the market structure of Singapore is highly concentrated, and the least concentrated banking market is Indonesia. On this note, the HHI results indicated that banks in Malaysia, Thailand and Philippines are operating in a monopolistic market and oligopolistic in the Singapore banking market. Generally, the most efficient banks were found in Thailand, Malaysia and Singapore with regard to technical efficiency scores. In the context of the sources of efficiency, the results of the study suggest that ASEAN banks are more scale efficient than pure technical efficiency. The findings imply that the bank management should target to utilize the banks inputs at the optimum level in order to keep their performance at the efficiency frontier.